80.7k views
5 votes
5x - 2y = 3
-5x + 4y = 9

User Itsnikolay
by
5.4k points

2 Answers

1 vote

Answer:

x = 3 / y = 6

Explanation:

5x - 2y = 3

-5x + 4y = 9

----------------- (combine the equations)

2y = 12

isolate the variable

y = 6

next, use one of the original equations and substitute in for y to solve for x

5x - 2(6) = 3

multiply

5x - 12 = 3

isolate the variable

5x = 15

divide each side by 5

x = 3

User PhilDulac
by
5.8k points
5 votes

The answer is (3,6) x=3 y=6

User Roger Urscheler
by
5.0k points